Nucleotide sequence and expression analysis of the Acetobacter xylinum uridine diphosphoglucose pyrophosphorylase gene. - Brede, G (1991)
The nucleotide sequence of the Acetobacter xylinum uridine diphosphoglucose pyrophosphorylase gene was determined; this is the first procaryotic uridine diphosphoglucose pyrophosphorylase gene sequence reported. The sequence data indicated that the gene product consists of 284 amino acids. This finding was consistent with the results obtained by expression analysis in vivo and in vitro in Escherichia coli.